KINERJA GURU DITINJAU DARI KUALITAS KEPEMIMPINAN, MOTIVASI KERJA DAN EFIKASI DIRI (Studi pada Guru SMP Negeri Se-Kecamatan Tawangsari Kabupaten Sukoharjo) - Sri Hartono (JURNAL ILMIAH EDUNOMIKA, 2020)
The Aims of the research are to know and analyze : (1) the effect of leadership qualities, work motivation and self-efficacy simultaneously on teacher performances; (2) the effect of leadership qualities on teacher performances; (3) the effect of work motivation on teacher performances; (4) the effect of self-efficacy on teacher performances of teachers of Government Junior High Schools in Tawangsari, Sukoharjo. The type of the research is descriptive quantitative research. The research was carried out in Sukoharjo. The population of the research were teachers of Government Junior High Schools in Tawangsari, Sukoharjo consisted 132 teachers. The research uses Proportional Random Sampling to choose sample in order to represent the penomena. The data collecting method were done using questionnaires and document techniques. The data was analyzed using multiple regression analysis. The conclusion of the analysis were : (1) there is a significant effect of leadership qualities, work motivation and self-efficacy simultaneously on teacher performances; (2) there is a significant effect of leadership qualities on teacher performances; (3) there is a significant effect of work motivation on teacher performances; (4) there is a significant effect of self-efficacy on teacher performances of teachers of Government Junior High Schools in Tawangsari, Sukoharjo. Keywords : Teacher Performances, Leadership Qualities, Work Motivation and Self-efficacy